ANALYSIS OF MATHEMATICAL LITERACY ABILITY IN TERMS OF STUDENT’S HABITS OF MIND - Rojabiah, Lulu Ul; Maryati, Tita Khalis; Firdausi, Firdausi (ALGORITMA: Journal of Mathematics Education, 2023)
AbstractMathematical literacy ability is an individual's ability to formulate, apply, interpret, solve problems, reason logically, communicate, and explain mathematics in solving everyday problems and sharing contexts. This paper describe result of research students' mathematical literacy skills, students' habits of mind, and determine the relationship between students' mathematical literacy abilities in terms of students' habits of mind. The method used in this research is descriptive quantitative with data collection techniques using test instruments and questionnaires. The subjects of this study were students of class VIII at an MTs Negeri in Jakarta with a sample of 110 students with cluster random sampling. Based on this research shown that there is a positive relationship between mathematical thinking habits and mathematical literacy skills. Students who already have good mathematical habits of mind are able to respond with awareness and strategies to get the right solution so as to improve the quality of mathematical literacy in solving problems in everyday life.. These results indicate that there is a significant relationship between students' mathematical literacy skills and mathematical thinking habits. AbstrakKemampuan literasi matematis merupakan kemampuan individu dalam merumuskan, menerapkan, menafsirkan, memecahkan masalah, menalar secara logis, mengkomunikasikan, dan menjelaskan matematika dalam pemecahan masalah sehari-hari dan berbagi konteks. Penelitian ini bertujuan untuk mendeskripsikan kemampuan literasi matematis siswa, mendeskripsikan kebiasaan berpikir matematis siswa, dan mengetahui hubungan kemampuan literasi matematis siswa  ditinjau dari kebiasaan berpikir matematis siswa. Subjek penelitian ini adalah siswa kelas VIII suatu MTs Negeri di Jakarta dengan sampel berjumlah 110 siswa. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dengan teknik pengumpulan data menggunakan instrumen tes dan angket. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara kebiasaan berpikir matematis dengan kemampuan literasi matematika. Siswa yang memiliki kebiasaan berpikir matematis yang baik mampu menyikapi dengan kesadaran dan strategi untuk mendapatkan solusi yang tepat sehingga meningkatkan kualitas literasi matematika dalam menyelesaikan masalah dalam kehidupan sehari-hari. Hasil tersebut menunjukan bahwa terdapat hubungan yang signifikan kemampuan literasi matematis siswa dengan kebiasaan berpikir matematis.